PENDAMPINGAN METODE PEMBELAJARAN AL-QUR’AN “QIRO’ATI” DI TAMAN PENDIDIKAN AL-QUR’AN NURUL HIDAYAH JAKENAN PATI JAWATENGAH - Syarifah Syarifah; Farida Isroani (LPPM Universitas Bina Bangsa, 2023)
Al-Qur'an is a guide for Muslims in the world and it is obligatory for us to studyit. Especially for young children is a very effective period to start learning the Qur'an. Learning alone is also not enough, it must require the method used, because learning without the right method does not guarantee good quality reading. Therefore theNurul Hidayah Al-Qur'an Education Park is a place for learning the Qur'an, using the Qiro'ati method as the application of learning. To find out the supporting factors and inhibiting factors in learning the Qur'an at TPQ Nurul Hidayah. This type of research uses qualitative research with a qualitative descriptive approach. Data collection techniques were taken from observation, interviews and documentation. The data analysis that the researcher uses is Miles and Huberman's analysis which includes 3 steps: data collection, data reduction, and data verification. The results of this study the researchers found that: 1. The implementation of the Qiro'ati method in learning the Qur'an at TPQ Nurul Hidayah was applied to the TIWAGAS (Conscientious, Alert, Firm) and DAKTUN (No Leading) teacher principles, as well as the LCTB student principle ( Smooth, Fast, Precise, Correct) and CBSA (Active Santri Learning Method) using the stages of preparation, organization, implementation, supervision and evaluation. 2. a. Supporting factors for this learning process include teachers who have already agreed, students' enthusiasm, parental support and adequate infrastructure. 2. b. Factors inhibiting the learning process include differences in the ability of students to pay attention to the teacher, lack of student discipline, differences in student enthusiasm for learning. learning discipline and always motivate students to always be enthusiastic about learning. Developing the learning process to be better and educating students as well as possible